Laporan Kasus : Tuberkuloma mimicking Tumor Paru - Zarfiardi Aksa Fauzi; Alven Edra; Hariadi Hatta (Fakultas Kedokteran Universitas Riau, 2022)
Pulmonary tuberculosis is a major public health problem in Indonesia, with the number of patients being the second largest in the world after India. Tuberculosis (TB) is caused by the pathogen Mycobacterium tuberculosis, 80% of which are pulmonary TB and the rest are extra pulmonary. Patients with a history of TB become one of the risk factors for lung cancer due to chronic tissue damage. Tuberculosis can also present as tuberculoma which can mimic a lung tumor. We report the case of a 55-year-old patient with complaints of a lump on the back since 3 months ago and weight loss of ± 9 kg in 5 months. The chest X-ray and CT scan showed an impression of a lung tumor and a TTNA examination was performed with the results of inflammatory cell infiltration of lymphocytes, neutrophils and macrophages. Cytology examination from the lump on the back came with the result of a cold abscess. A frozen section-open biopsy was performed with macroscopic of caseating necrosis and histopathology results showed the presence of Langhans cells, typically tuberculosis. Currently, the patient treated with ATD first category regimen for 6 months as definitive therapy of tuberculosis.